Work-Life Challenges of Working Women in Kathmandu - Pokharel, Sharmila (Interdisciplinary Issues in Education, 2024)
In a developing country like Nepal, patriarchal beliefs dominated women’s empowerment and opportunities for women were limited. Gradually, with the development of society and social attitudes, women took over diverse roles and women began to experience better autonomy and self-esteem. Despite social progress and increasing opportunities, traditional expectations add many challenges to the lives of working women. Seven working women from different sectors were selected for the convenience sampling which was a part of the qualitative approach to study to expose the challenges of working women in balancing work and life in Kathmandu district. For the collection of information, semi-structured interview guide was used which helped in the identification of key challenges for working women such as triple burden, family expectations, gender-based discrimination and abuse etc. The study was conducted fromDec 2023 to March 2024. The findings revealed that the women’s difficulty in achieving work-life balance is intensified by social pressures, including reproductive roles and patriarchal norms. Trained relationships and internal family conflicts are the major outcomes of unbalanced work-life. The findings also highlighted the parameters that are needed for the support of the women in the Kathmandu Valley to achieve a fair and satisfactory balance in their work life. The critical need for comprehensive policy reforms, cultural change and legal protection to mitigate the ’triple burden’ and promote gender equality in work-life is focused on the experience of Nepalese working women.